2020
DOI: 10.1111/1365-2745.13409
|View full text |Cite
|
Sign up to set email alerts
|

Community‐level interactions between plants and soil biota during range expansion

Abstract: Plant species that expand their range in response to current climate change will encounter soil communities that may hinder, allow or even facilitate plant performance. It has been shown repeatedly for plant species originating from other continents that these plants are less hampered by soil communities from the new than from the original range. However, information about the interactions between intra‐continental range expanders and soil communities is sparse, especially at community level. Here we used a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
3
17
0
1
Order By: Relevance
“…The different responses of bacterial and fungal diversity in our study are in line with previous findings in the Jena Experiment (e.g. Dassen et al., 2017; Lange et al., 2015) and may indicate different specificity of interactions between plants and soil bacteria and fungi or competition between taxa of bacteria and fungi (Bahram et al., 2018; Koorem et al., 2020). The fungal communities in old soils could have represented specialized subsets of fungal species particularly suited for the corresponding plant community (Semchenko et al., 2018; Sosa‐Hernández et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The different responses of bacterial and fungal diversity in our study are in line with previous findings in the Jena Experiment (e.g. Dassen et al., 2017; Lange et al., 2015) and may indicate different specificity of interactions between plants and soil bacteria and fungi or competition between taxa of bacteria and fungi (Bahram et al., 2018; Koorem et al., 2020). The fungal communities in old soils could have represented specialized subsets of fungal species particularly suited for the corresponding plant community (Semchenko et al., 2018; Sosa‐Hernández et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to bacterial richness, soil legacy did not increase fungal richness and even decreased fungal evenness. The different responses of bacterial and fungal diversity in our study are in line with previous findings in the Jena Experiment (e.g., Dassen et al, 2017; Lange et al, 2015) and may indicate different specificity of interactions between plants and soil bacteria and fungi or competition between taxa of bacteria and fungi (Bahram et al, 2018; Koorem et al, 2020). The fungal communities in old soils could have represented specialized subsets of fungal species particularly suited for the corresponding plant community (Semchenko et al, 2018; Sosa-Hernández et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Future studies should test the effect of soil communities from different locations within both ranges to validate the general nature of the patterns reported here. However, our results are in line with previous studies showing that soil communities from multiple locations in the original and new range have similar effect on the biomass production of rangeexpanding plant communities during soil conditioning (Koorem et al 2018) and feedback phase (Koorem et al 2020). The effect of soil communities reported in experimental studies may at least partly depend on the methodological approach (Wang et al 2018), in this study demonstrated by the negative effect of non-target soil microbes found in Experiment I that was not confirmed in Experiment II.…”
Section: Discussionsupporting
confidence: 93%